Quando l’amore... non è amore. Quale cultura contro la violenza - Vari, Autori (Il sogno della farfalla, 2015)
The aim of the homonymous meeting-debate held in Rome on in December 2014 was to reflect on the deep seated causes of violence against women and on ways of intervening so as to prevent and fight it, in particular on a cultural level. The participants were professionals and specialists who work in cooperatives and associations active within schools and in the health system, in anti-violence units, in the fight against the mafia, in clinics; teachers, writers and journalists; anthropology scholars, both regional and national politicians. The themes treated were many and interrelated: the violence against women as a historical-cultural rather than natural phenomenon; femicide as the final result of psychic violence; the language used by the mass media which is often sensationalistic and incorrect; the rejection of the catholic view of women’s roles; the idea that human sexuality should not be seen as necessarily linked to procreation; interventions that favour women and children who are victims of domestic violence; the topicality of the Istanbul Convention. The talks revealed the need for strong cultural change that stops viewing women as inferior human beings and considers the relationship between the sexes free from cultural and religious conditioning. The work for prevention among young people is a central issue and not seen as instruction/repression but as development and knowledge which aims to fight the diffusion of violent and pathological ideologies. Many speakers referred to the scientific theories of the Italian psychiatrist Massimo Fagioli on human nature and the natural equality of human birth, theories which give rise to a new idea of sexuality.